DIGITALIZATION ON EDUCATION: EXPLORING THE IMPACT AND ADAPTATION - Chandra, Frederick (Jurnal Review Pendidikan dan Pengajaran, 2025)
Digitalization is rapidly changing education across the world, including Cendekia Harapan School in Bali. The research analyses digital tools usage in schools, and their benefits and challenges. On the basis of qualitative methods, such as document analysis, expert interview, survey, and literature review, the study analyzes how teachers and students assist with the process of digitization at school. The findings show that technology enhances lesson planning, facilitates students in learning with the help of interactive tools, and enhances progress tracking through systems such as Moodle. On the other hand, some challenges are resource limitation, teacher adaptation, and over dependence on technology. Schools address these issues through training programs, better access to resources, and policies for encouraging responsible technology use. This research has pointed out the need to balance digital tools with traditional learning so that all students benefit while still developing critical thinking skills. The study provides an overview of how to improve digital education in Bali and other regions facing similar challenges.